METHODOLOGY OF TEACHING MATHEMATICS IN PRIMARY EDUCATION - Mardanov Eshim Muratovich; Mardanova Mehribon; Egamova Anora (Web of Journals Publishing, 2024)
This article explores the various methodologies employed in teaching mathematics in primary education. It delves into the theoretical foundations, practical applications, and effectiveness of different teaching strategies. The study emphasizes the importance of a solid mathematical foundation in early education and provides insights into best practices for educators.
Keywords: Mathematics education, primary education, teaching methodologies, pedagogy, early childhood education, educational strategies.